Analysis of the Application of Sharia Economics to the Determination of Selling Prices for MSMEs in the Banyu Anget Tirta Husada Tourism Area, Pacitan Regency (Case Study on the Banyu Anget Tirta Husada Tourism Area) - Irfan Miranda; Retno Ayu Cahyoningtyas; Fitri Andriyani; Syaiful Ma'ruf (Journal of Creative Power and Ambition (JCPA), 2026)
This research is motivated by the dynamics of MSME selling price determination in tourist areas, which are often flexible and do not fully consider the principles of fairness and transparency. This practice is important to examine from a sharia economic perspective, which emphasizes honesty, openness, and the prohibition of elements of ambiguity in transactions. This study aims to analyze the selling price determination mechanism of MSMEs and assess its compliance with sharia economic principles in the Banyu Anget Tirta Husada Tourism area in Pacitan Regency. The approach used is a qualitative case study method. Data were obtained through in-depth interviews, field observations, and documentation of MSMEs, tourism managers, and consumers. The results show that pricing is still based on simple calculations that consider raw material costs, demand, location, and tourist visit conditions. The application of sharia economic principles is evident in aspects of honesty and efforts to maintain fair profits, but is not optimal in the aspects of transparency and price clarity, thus still potentially containing elements of gharar. These findings emphasize the importance of strengthening the understanding and practice of sharia economics in pricing to create fair, transparent, and sustainable transactions.